(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The present paper studies the product placement in de current advertising enviroment. If this innovation is not applied a new way of advertising it could produce alack of communication and the companies could loss important opportunities. The paper concludes with several points related to the definition of the concept and there commendation for its implementation.